Abe Lincoln, the young years - Brandt, Keith, 1949-; Lawn, John (Mahwah, N.J. : Troll Associates, 1982)
Focuses on events from Abraham Lincoln's youth in Kentucky and Indiana which proved influential in his later life.
School Library Journal.
4.8
3-6
Keywords: Lincoln, Abraham, -- 1809-1865 -- Childhood and youth -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents -- United States -- Biography; Presidents -- United States -- Biography